Relationship between the chemical composition of two divergent veld types in the Karroo and the productivity of merino sheep - Louw, Gerrit Nieuwoudt (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1962.